Exploration of Dynamics of Corporate Performance and Corporate Governance - Saebah, Nur; Merthayasa, Alit; Azzahra, Adelia; Rahayu, Riska (Ridwan Institute, 2023)
This research explores the dynamics of corporate performance and governance in the context of globalization and fierce business competition. With a focus on the Spanish tourism sector and evaluating corporate governance in Latin America, the study uses a mixed approach, combining qualitative and quantitative analysis. The study aimed to understand the relationship between corporate performance and corporate governance by exploring the differences between family and non-family businesses. The research provides insight into how ownership, management, and governance practices can affect corporate performance through literature studies, return on capital analysis, and corporate governance evaluations. The results show that family businesses have unique dynamics involving emotional involvement and creativity, while good corporate governance is concerned with consistency of return on capital. Implications include a better understanding for organizational leaders in making investment decisions and sustainable business strategies. This research makes theoretical and practical contributions to understanding performance dynamics and corporate governance in global and local business contexts.